Bisubstrate multi-colorimetric assay based on the peroxidase-like activity of Cu2+-triethylamine complex for copper ion detection. (February 2023) - Zhou, Hang-Yu; Chai, Tong-Qing; Peng, Li-Jing; Zhang, Wei-Yi; Tian, Tao; Zhang, Hao; Yang, Feng-Qing
Abstract: A bisubstrate colorimetric system was developed for rapid and multi-color assay of copper ion (Cu 2+ ). Cu 2+ -triethylamine (Cu 2+ -TEA) complex with the peroxidase-like activity can catalyze the 3, 3′, 5, 5′-tetramethylbenzidine (TMB) to produce oxidized TMB (TMB +, color in blue) and dopamine (DA) to oxidized DA (oxDA, color in orange) in the presence of hydrogen peroxide, which can obtain a three-color colorimetric result due to the couple of complementary colors of blue and orange. The determination of Cu 2+ is achieved based on the absorbance value at 460 nm of the composite peak of TMB + and oxDA. After systematically optimizing the reaction conditions, the developed bisubstrate colorimetric method exhibits high sensitivity for the detection of Cu 2+ (limit of quantitation (LOQ) is 0.0625 μM) with a wide linear range of 0.0625–8.0 μM (R 2 = 0.991). Meanwhile, the reaction solution shows an orange, brown, and green color change with the increase in Cu 2+ concentration, which can realize the semi-quantitatively detection by the naked eyes. Furthermore, TMB was also used as a single substrate for Cu 2+ detection with a linear range of 0.5–9.0 μM (R 2 = 0.994), and the LOQ is determined to be 0.5 μM. The LOQ of bisubstrate system is 8 times lower than that of single substrate system, indicating a higher sensitivity for the detection of Cu 2+ using the bisubstrate colorimetric system. In addition, the developed bisubstrate colorimetric method exhibits excellent selectivity for Cu 2+ detection, which was applied in the determination of Cu 2+ in lake water and soil samples, and satisfactory spiked recoveries were obtained. Graphical abstract: Image 1 Highlights: Cu 2+ -triethylamine (TEA) complex exhibits excellent peroxidase-like activity. A bisubstrate (TMB + dopamine) colorimetric sensor is developed based on Cu 2+ -TEA complex. The developed senor displays three-color change for the detection of Cu 2+ . The bisubstrate sensor shows a higher sensitivity than that of single substrate.